MORTALITY DUE TO GARBAGE CODES IN BRAZILIAN MUNICIPALITIES: DIFFERENCES BETWEEN DIRECT AND INDIRECT ESTIMATES IN 2015 TO 2017 - Teixeira , Renato Azeredo (2020)
Objectives: the present study aims to generate estimates of mortality rates due to garbage codes (GC) for municipalities in Brazil by comparing direct and indirect methods, based on deaths registered in the Mortality Information System (SIM) between 2015 and 2017. Methods: Data from the SIM were used. The analysis was performed in groups of GC, levels 1 and 2, levels 3 and 4 and total GC. Mortality rates were estimated directly and indirectly, Empirical Bayesian Estimators. Results: about 38% of CG were estimated and regional differences in mortality rates were observed, higher in the Northeast and Southeast and lower in the South and Midwest. The Southeast presented similar rates for the two groups of CG analyzed. The smallest differences between direct and indirect estimates were observed in large cities, above 500 thousand. The municipalities in the north of Minas Gerais and the states of Rio de Janeiro, São Paulo and Bahia presented municipalities with high rates at levels 1 and 2. Conclusion: there are differences in the quality of the definition of the underlying causes of death, even with the use of indirect methodology which assists in smoothing rates. The quality of the definition of causes of death is important since they are associated with the access and quality of health services and offer subsidies for health planning.